PENGARUH PENGGUNAAN MEDIA MANIPULATIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Helmina, Welly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this reasearch is to investigate whether or not the use of â€œManipulative Mediaâ€ effective toward the studentsâ€™ achievement in learning mathematic on the fifth grade students of SDN 28Â  Pontianak Kota. This research applied a quasi-experimental design. The population of this research was V A as the experimental group and V B as the control group which tottaly consist of 73 students. The research findings showed that the score of V A was 72.75, while V B got 65.43. Based on the measurement parametricÂ  statistic, the result of t-test (2.198) > t-table (1.669). Thus, the alternative hypothesis (Ha) was accepted. Based on the analyse, there is a difference mean score of studentsâ€™ achievement between using pictures and using manipulative media. The effectiveness of manipulative media towards the studentsâ€™ achievement in mathematic Â on fifth grade was 0,53 which categorized as medium. Keywords: Effect, Manipulative Media, Studentsâ€™ Achievment in Mathematic